2023
DOI: 10.3390/plants12203615
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Responses to Manganese Toxicity in Soybean Roots and Leaves

Yanyan Wang,
Jianyu Li,
Yuhu Pan
et al.

Abstract: Soybean is one of the most crucial beans in the world. Although Mn (manganese) is a kind of important nutritive element helpful to plant growth and health, excess Mn is harmful to crops. Nevertheless, the effect of Mn toxicity on soybean roots and leaves metabolism is still not clear. To explore this, water culture experiments were conducted on the development, activity of enzyme, and metabolic process of soybeans under varying levels of Mn treatment (5 and 100 μM). Compared with the control, the soybeans unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 76 publications
0
14
0
Order By: Relevance
“…Mn toxicity occurs when the available Mn content in the soil exceeds the typical Mn concentration required by the plant. Plants show evident evidence of poisoning on their leaves as a consequence, such as dark spots, crinkled leaves, and chlorosis; Mn poisoning also affects roots, resulting in a decrease in lateral root count and dry weight, in addition to the signs found on the leaves [33]. The findings in this study revealed that AhMDHs are differentially expressed in the roots and leaves of peanut subjected to Mn toxicity stress.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Mn toxicity occurs when the available Mn content in the soil exceeds the typical Mn concentration required by the plant. Plants show evident evidence of poisoning on their leaves as a consequence, such as dark spots, crinkled leaves, and chlorosis; Mn poisoning also affects roots, resulting in a decrease in lateral root count and dry weight, in addition to the signs found on the leaves [33]. The findings in this study revealed that AhMDHs are differentially expressed in the roots and leaves of peanut subjected to Mn toxicity stress.…”
Section: Discussionmentioning
confidence: 52%
“…When the available Mn content in the soil exceeds the normal Mn concentration needed by a plant, the plant is likely to suffer from Mn toxicity. Plants, as a result, display obvious signs of poisoning on their leaves, such as dark patches, crinkled leaves, and chlorosis; Mn poisoning also affects roots, resulting in reduced lateral root count and dry weight, in addition to the signs on the leaves [33]. Excess Mn prevents the absorption and transfer of other essential elements, such as calcium, magnesium, iron, and phosphorus, possibly because of the similar ionic radii or binding strength of ligands [34].…”
Section: Introductionmentioning
confidence: 99%
“…The NRAMP family is highly important for metal absorption and transportation in plants, with most AhNRAMPs being primarily expressed in androecia, roots, and immature seeds [ 55 ]. MTPs are also vital for bivalent cation transport in plants [ 86 ]. Previous studies have linked NRAMPs and MTPs to the transportation of bivalent metal ions such as Fe 2+ and Cd 2+ [ 55 , 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…The dry root samples (0.15 g) were completely dissolved in nitric acid (Guangzhou Reagent, Guangzhou, China). The levels of Al, Mg, Na, K, Fe, Ca, Mn, Zn, Cu, and Se in peanut roots were tested using PS7800 ICP–AES (inductively coupled plasma atomic emission spectrometry) (Hitachi, Tokyo, Japan) [ 86 , 97 ]. Each index was analyzed using three biological replicates.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, Nazari et al (2018) reported that progressively increasing Mn concentrations in Mentha aquatica plants simultaneously increased the contents of flavonoids, anthocyanins, malonaldehyde (MDA), hydrogen peroxide (H 2 O 2 ), and activated antioxidant enzymes, such as SOD, CAT, and APX (Nazari et al, 2018). Apart from the antioxidant mechanisms, plants also cope with Mn toxicity by deploying or activating their tolerance mechanisms via regulation of Mn uptake (transport), translocation, and distribution within the plant cells (Wang et al, 2023). Some of these transporters (transport mechanisms) have been reported and include AtNramp1, and AtNramp3, OsNramp1, and OsNramp5, identified in Arabidopsis and rice, respectively (Socha and Guerinot, 2014;Chang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%